2022
DOI: 10.1111/pbr.12994
|View full text |Cite
|
Sign up to set email alerts
|

Breeders' Sensory Test: A new tool for early selection in breeding for tomato (Solanum lycopersicum) flavour

Abstract: For several decades, improved flavour has not been a main focus in tomato breeding because it is difficult and expensive to evaluate. Sensory panels are designed to assess flavour, but they are not able to evaluate large sample numbers typical for early breeding generations. Selection in the first segregating generation could enhance breeding for flavour by preventing the loss of favourable alleles. The efficiency of early selection is unknown due to the polygenetic inheritance of flavour. To address these iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Despite their obvious advantages regarding number of cultivars and, more importantly, the time required for analysis, field evaluations are generally subjective and prone to error because they are usually based on the sensory preferences of one or few individuals ( 39 ). However, Hagenguth et al ( 36 ) demonstrated a highly significant correlation of sweetness and TSS and sourness and TA, indicating the efficiency of the breeders’ sensory test. A trained panel may not able to assess a large number of samples in a short time, which is typical for early breeding generations, for example, that also require replications ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite their obvious advantages regarding number of cultivars and, more importantly, the time required for analysis, field evaluations are generally subjective and prone to error because they are usually based on the sensory preferences of one or few individuals ( 39 ). However, Hagenguth et al ( 36 ) demonstrated a highly significant correlation of sweetness and TSS and sourness and TA, indicating the efficiency of the breeders’ sensory test. A trained panel may not able to assess a large number of samples in a short time, which is typical for early breeding generations, for example, that also require replications ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Hagenguth et al ( 36 ) demonstrated a highly significant correlation of sweetness and TSS and sourness and TA, indicating the efficiency of the breeders’ sensory test. A trained panel may not able to assess a large number of samples in a short time, which is typical for early breeding generations, for example, that also require replications ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations